A Method to Provide High Volume Transaction Outputs Accessibility to Vision Impaired Using Layout Analysis - Nazemi, Azadeh; Murray, Iain; McMeekin, David A. (Transactions on Engineering and Computing Sciences, 2014)
The Documents in the financial services, insurance, utilities, and government sectors typically require a high volume of PDF documents to be generated which are stored for presentment or archived for legal purposes. As high volume transactional output (HVTO) demands put increasing pressure on online presentment capabilities, accessibility has become a growing concern. In particular, access to these files proposes significant challenges when these documents are presented to visually impaired people using assistive technologies (i.e. screen readers). Since it is rare that all recipients are prepared to accept electronic delivery of their documents, a large portion of the documents is still printed as PDFs. In an online billing system, bills are sent to customers’ email accounts as attached PDF files or HTML links. These bills in the most cases are neither accessible through assistive technologies nor useable by vision-impaired customers. This paper provides a method for HVTO documents automatic transformation to an accessible and navigable Mark-up format such as XML or Digital Accessible Information System (DAISY).